Pengaruh Motivasi Belajar dan Pengetahuan Keteknikan Terhadap Keterampilan Peserta Didik dI SMK Negeri 1 Enrekang - Putri Nanda Sari; Yuanita B; Muh Ardi; Abdul Muis Mappalotteng (Sakura Digital Nusantara, 2023)
This study aims to discover (1) Engineering knowledge, learning motivation, school environment, and students’ skills at SMK Negeri 1 Enrekang, (2) the influence of engineering knowledge on students’ skills at SMK Negeri 1 Enrekang, (3) the influence of motivation on students’ skills at SMK Negeri 1 Enrekang. This type of research used quantitative research with a correlational approach The sampling technique used was a cluster random sampling technique. The analysis employed descriptive statistical analysis and inferential statistical analysis, namely the requirements analysis test and linear regression test. The results of this study indicate that (1) the results of descriptive statistical analysis show that engineering knowledge is in Very High category, the learning motivation is in Very High category, the school environment is in Very Good category, and the skills are in Very High category, (2) there is a positive and significant influence of knowledge engineering on students’ skills at SMK 1 Enrekang, (3) there is a positive and significant influence of learning motivation on students’ skills at SMK Negeri 1 Enrekang.